2018
DOI: 10.1055/a-0630-2079
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Collagenase-Inhibiting Flavonoid from Alchemilla vulgaris Using NMR-Based Metabolomics

Abstract: This paper describes the use of H NMR profiling and chemometrics in order to facilitate the selection of medicinal plants as potential sources of collagenase inhibitors. A total of 49 plants with reported ethnobotanical uses, such as the healing of wounds and burns, treatment of skin-related diseases, rheumatism, arthritis, and bone diseases, were initially chosen as potential candidates. The collagenase inhibitory activity of hydroalcoholic extracts of these plants was tested. Moreover, their phytochemical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
(35 reference statements)
0
17
0
1
Order By: Relevance
“…This workflow has already been applied successfully in several areas of research, from human diagnostics and epidemiology to the plant sciences [ 14 ]. In this latter field of study, metabolomics was successful at facilitating the identification of the active components of medicinal plants [ 15 ], studying plant ecotypes and biological features [ 16 , 17 ], and controlling food and botanical quality, both in terms of nutraceutical/biological properties and fraud detection [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This workflow has already been applied successfully in several areas of research, from human diagnostics and epidemiology to the plant sciences [ 14 ]. In this latter field of study, metabolomics was successful at facilitating the identification of the active components of medicinal plants [ 15 ], studying plant ecotypes and biological features [ 16 , 17 ], and controlling food and botanical quality, both in terms of nutraceutical/biological properties and fraud detection [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This workflow proved to be successful in several research fields, from human diagnostics and epidemiology to plant science (Wolfender et al, 2015; Anđelković et al, 2017), where it resulted particularly helpful to face the challenges posed by the complexity of natural product chemistry (Pauli et al, 2012). For instance, metabolomics has been employed to facilitate the identification of medicinal plants active principles (Gođevac et al, 2018; Mandrone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the activity of this compound as a collagenase inhibitor was higher than doxycycline, a Federal Drug Administration (FDA)-approved drug, used as a positive control in this study. It might be added that aside from wound or burn healing, collagenase inhibitors might be useful in the treatment of other skin-related diseases, such as dermatitis, acne, urticarial, or photoaging (Mandrone et al, 2018). Also, Vlaisavljević et al (2019) revealed amylase and tyrosinase inhibitory effects of A. vulgaris, which might be related to antidiabetic and skin-related diseases (Vlaisavljević et al, 2019).…”
Section: Wound Healingmentioning
confidence: 99%